2006
DOI: 10.1177/08830738060210021901
|View full text |Cite
|
Sign up to set email alerts
|

Right Hemisphere Brain Morphology, Attention-Deficit Hyperactivity Disorder (ADHD) Subtype, and Social Comprehension

Abstract: Social comprehension involves empathy for others' experiences and appropriate responses to nonverbal cues. Previous research using magnetic resonance imaging (MRI) has suggested a relationship between brain morphology and psychiatric syndromes, such as attention-deficit hyperactivity disorder (ADHD), that typically entail social difficulties. The right hemisphere, specifically, has been associated with social skill deficits, and numerous studies have also associated ADHD with social skill deficits. No studies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…The Social Participation subtest of the SPM "measures social activities in the home and the community" (Parham & Ecker, 2007, p. 20), a construct that developers of the SPM acknowledge as one that is often impacted by sensory processing dysfunction but also that is, at times, impacted by reasons unrelated to sensory processing. For example, social difficulties are well documented among children diagnosed with ADHD (Miller et al, 2006). Our study did not determine whether the relationships were specific to sensory processing differences or other constructs.…”
Section: Discussionmentioning
confidence: 78%
“…The Social Participation subtest of the SPM "measures social activities in the home and the community" (Parham & Ecker, 2007, p. 20), a construct that developers of the SPM acknowledge as one that is often impacted by sensory processing dysfunction but also that is, at times, impacted by reasons unrelated to sensory processing. For example, social difficulties are well documented among children diagnosed with ADHD (Miller et al, 2006). Our study did not determine whether the relationships were specific to sensory processing differences or other constructs.…”
Section: Discussionmentioning
confidence: 78%
“…Multiple aberrations in the brains of children with ADHD have been documented (see Konrad & Eickhoff, 2010 for a comprehensive review), some of which may account for problematic language skills. For instance, preliminary neuroimaging studies have found that children with ADHD have smaller bilateral cerebral volume, which is associated with receptive language difficulties (Kibby, Pavawalla, Fancher, Naillon, & Hynd, 2009); atypical pars triangularis, which is related to expressive language function (Kibby, Kroese, Krebbs, Hill, & Hynd, 2009); and atypical right hemisphere brain morphology, which is associated with poorer social comprehension (Miller, Miller, Bloom, Hynd, & Craggs, 2006). However, a comprehensive neuroimaging analysis of the language networks in children with ADHD is yet to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Social skills deficits are also common in ADHD (Wheeler Maedgen & Carlson, 2000), and some have suggested that “social inattention” – or difficulty attending to social cues – may be an additional feature of ADHD. In addition, it has been posited that ADHD is associated with risk for social comprehension deficits, particularly in those with atypical right hemisphere morphology (Miller, Miller, Bloom, Hynd, & Craggs, 2006). Thus, there is some evidence for abnormal right hemisphere functioning in ADHD (Hale, Bookheimer, McGough, Phillips, & McCracken, 2007; Swartwood, Swartwood, Lubar, & Timmermann, 2003), and clear evidence for the importance of the right hemisphere in emotional prosody.…”
Section: Discussionmentioning
confidence: 99%